Dampak Pernikahan Usia Dini di Kalangan Masyarakat - Khofifah Indah; Rizki Juliana; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The higher the number of early marriages, it means that the empowerment regarding the regulations imposed by the government is still low. Social views regarding early marriage in Indonesia are one of the factors that often occur, both early marriages that occur in rural and urban areas. This is due to mindset. people who are still simple so this problem will continue to occur.Marriage is generally carried out by adults regardless of occupation, religion, ethnicity, poverty or The rich live in the village or in the city. Age of marriage at a young age causes many factors divorce because she doesn't know how to take responsibility for home lifeladder. Early marriage creates problems, both from the perspective of complications of Islamic law. Keywords: Impact, Marriage, Early Age, Community